Central Controller Framework for Mobile Cloud Computing and Security Issues - Sk Mahaboob Sharif, Sk; V.V Satyanarayana, K; Harsha vardhan, M; Harika, V (International Journal of Engineering and Technology, 2018)
Cloud Computing is an on demand service where resources like online office software and on-line storage are made available as per the users requirement. The word cloud in cloud computing is used as a symbol for internet since it offers various computing services as well as resourcesÂ like storage, servers, platforms Â and applications are provided to devices over the internet. Mobile cloud computing joins the cloud computing with mobile computing and giving the shopper with limitless pool of useful resource from cloud without hampering mobility of consumer. The mobile cloud computing generation is developing rapidly many of the customers and at the equal time it introduces the early protection threats inside. A mobile user storing data on the cloud can be read by the cloud service provider or hacked by man-in-middle attack, thus affecting consumer privateers and integrity. So information saved on the cloud have to be encrypted, disallowing unauthorized user to access saved records. Mobile devices are resource constrained since they are battery powered, have less processing power and have less storage space. Any set of rules or technique used for securing mobile users statistics have to don't forget above constraints for powerful makes use of cloud for portable clients. Most of the mobile devices have nearly equal functionalities, so mobile devices will face some problems associated with security and third parties, by this paper we have given a review of different techniques for secure storage of mobile userâ€™s data in the cloud, their merits and demerits for mobile environment.Â Â